Observation of B meson decays to ωk* and improved measurements for ωρ and ωf0 - Aubert, B; Karyotakis, Y; Lees, J; Poireau, V; Prencipe, E; Prudent, X; Tisserand, V; Garra Tico, J; Grauges, E; Lopez, L; Palano, A; Pappagallo, M; et al. (2009)
We present measurements of B meson decays to the final states ωK*, ωρ, and ωf0, where K* indicates a spin 0, 1, or 2 strange meson. The data sample corresponds to 465×106 BB̄ pairs collected with the BABAR detector at the PEP-II e+e- collider at SLAC. B meson decays involving vector-scalar, vector-vector, and vector-tensor final states are analyzed; the latter two shed new light on the polarization of these final states. We measure the branching fractions for nine of these decays; five are observed for the first time. For most decays we also measure the charge asymmetry and, where relevant, the longitudinal polarization fL. © 2009 The American Physical Society.